MMWR. Morbidity and mortality weekly report, Vol. 42, no. 20, May 28, 1993 - Centers for Disease Control and Prevention (U.S.)
Update: Influenza activity--United States, 1992-93 season -- Lead poisoning in bridge demolition workers--Georgia, 1992 -- Sexual behavior and condom use--District of Columbia, January-February 1992 -- Childbearing patterns among selected racial/ethnic minority groups - United States, 1990.